2019
DOI: 10.1113/jp277447
|View full text |Cite
|
Sign up to set email alerts
|

Physiological properties of the lamina I spinoparabrachial neurons in the mouse

Abstract: Key points Spinal cord lamina I neurons receiving dense input from nociceptors and projecting to the parabrachial area at the ponto‐mesencephalic junction form the major ascending pain‐related pathway in rodents. Lamina I spinoparabrachial (SPB) neurons have never been characterized in mice, despite the growing and extensive use of this species to understand the contribution of lamina I SPB neurons in chronic pain. The electrophysiological properties of lamina I SPB neurons recorded here in anaesthetized mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 51 publications
(130 reference statements)
17
34
0
Order By: Relevance
“…In these initial experiments, we recorded from and characterized 34 retrogradely-95 labeled lamina I SPB neurons. Consistent with previous studies (Allard, 2019 None of these SPB neurons responded to heat alone. In contrast, ~25% (8 of 34) 100 responded selectively to cold ( Figures 1B and 1C).…”
Section: Identification Of Cold-selective Spb Neurons 83supporting
confidence: 92%
See 2 more Smart Citations
“…In these initial experiments, we recorded from and characterized 34 retrogradely-95 labeled lamina I SPB neurons. Consistent with previous studies (Allard, 2019 None of these SPB neurons responded to heat alone. In contrast, ~25% (8 of 34) 100 responded selectively to cold ( Figures 1B and 1C).…”
Section: Identification Of Cold-selective Spb Neurons 83supporting
confidence: 92%
“…In particular, extracellular 69 recording from cat and monkey spinal cord in vivo has revealed the existence of 70 spinothalamic tract (STT) neurons that respond to cold stimulation to the skin, but not 71 other somatosensory modalities Craig and Dostrovsky, 2001;Craig 72 and Hunsley, 1991;Craig and Kniffki, 1985;Dostrovsky and Craig, 1996;Zhang et al, 73 2006). In rodent, we and others have described spinoparabrachial (SPB) neurons that are 74 cold-selective (Allard, 2019;Andrew, 2009;Hachisuka et al, 2016). In this study, we 75 identified cold-selective output neurons and then further examined whether they show 76 distinctive features indicative of a distinct subtype of SPB neuron.…”
Section: Introduction 45mentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, extracellular recording from cat and monkey spinal cord in vivo has revealed the existence of spinothalamic tract (STT) neurons that respond to cold stimulation to the skin, but not other somatosensory modalities [11][12][13][14]18,56]. In rodent, we and others have described spinoparabrachial (SPB) neurons that are cold-selective [1,4,22]. However, it remained unclear whether these neurons are cold-selective simply as function of wiring, or whether these cells are a unique cell type, representing a discrete output channel for somatosensation.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one of the key challenges is that most spinal output neurons respond to several types of stimuli. For instance, the majority of temperature-responsive spinal output neurons also respond to mechanical input [1,10,14,21]. Similarly, all spinal output neurons that appear to be tuned for itch also respond to the noxious chemicals mustard oil and capsaicin [5,16,28].…”
Section: Introductionmentioning
confidence: 99%